PENGARUH KUALITAS LAYANAN TERHADAP PRODUKTIVITAS KERJA PEDAGANG KAKI LIMA NOTOHARJO - Mulyanto . (KELOLA, 2013)
The policy structuring location five-foot trader set by the local government, of course has the effect or impact on the vendors themselves and also for the environment. based on two criteria are used, internal and external. Internal is how the impact on street vendors in terms of economic improvement, a sense of justice and that is how the relationship with the external environment. Impact on the environment implies a positive environment that is well-organized, with waste treatment market, greening around the relocation market, so the market environment will be beautiful and doesn’t look shabby (environmentally friendly). While the negative impact of the decline in capital and revenue, increased operating costs, declining market activities (production, distribution and consumption), weakening of social networks (customers) and declining merchant opportunity to participate in social groups of non-formal. Therefore, further research requiredFrom the research conducted showed that the quality of service significantly influence the arrangement of locations although its low and have strong and significant affect on working productivity of Notoharjo’s five-foot trader Surakarta. And also the arrangement of locations has lower significant effect on working productivity althought it's lower on Notoharjo’s five-foot trader of Surakarta. Keywords: quality of service, working productivity, arrangement of location